Predefined-Performance Sliding-Mode Tracking Control of Uncertain AUVs via Adaptive Disturbance Observer - Yuhang Guo; Zijun Gao; Yuhang Hu; Zhankui Song (Journal of Marine Science and Engineering)
In this paper, a sliding-mode control strategy incorporating prescribed features was systematically designed, resolving the dual challenges of trajectory tracking precision maintenance and disturbance attenuation for an AUV subjected to dynamic model inaccuracies and disturbances. To neutralize the impact of parametric uncertainties and environmental disturbances on the controlled plant, an adaptive finite-time sliding-mode disturbance observer (AFTSMDO), the upper bound of perturbations was not required for the proposed observer. Subsequently, by embedding error transformations and prescribed performance functions, we designed a novel sliding-mode surface. This surface ensured that tracking errors and their derivatives converge to specified regions within predefined temporal bounds, irrespective of initial configurations. This overcomes the longstanding limitations of traditional prescribed performance control methods and contributes to enhancing system performance. Finally, we conducted comparative simulation experiments with existing sliding-mode control methods to prove the practical viability and comparative advantage of the synthesized control methodology.